O papel das relações interpessoais na condução do ProSavana-JBM (Japão-Brasil-Moçambique): um estudo de caso: programa de Cooperação Triangular para o Desenvolvimento Agrícola da Savana Tropical de Moçambique - Ferreira, Melina de Souza-Bandeira (2012)
This case study intends to report how interpersonal relationships might have played an important role on making ProSAVANA-JBM work. (Triangular Cooperation Program for Agricultural Development of the African Tropical Savannah in Mozambique-Japan-Brazil-Mozambique). The intermediary objectives contribute to for one to look into which other factors might have been determinant for realization of ProSAVANA. This program not only represents an international partnership between organizations of three countries: Brazil, Japan and Mozambique, but also has impacts of a social, economic and environmental nature. The data analysis shows that interpersonal relationships outstands among the other determining factors on the Programa realization, and corroborates for the design of an interpersonal relationship network’s model related to ProSAVANA. This study’s limitation refere to the difficulty on replicating or generalizing this study on a scientific basis, considering the fact that it wouldn’t be possible to imply on evaluations on a certain behavior exclusively based on a single case study. Finally, the purpose of this study is to offer theoretical and empirical tools that enable an in-depth assessment on the role played by interpersonal relationships, and also to contribute to bridging the gaps in the field of business and public administration.